Comparative cytotoxicity of in vitro and field grown shoots of Withania somnifera in Caenorhabditis elegans model - Santhanu, Krishnapriya; Parameshwari, D.; Natarajan, Kanimozhi; Vinod, Sangeetha; Senthil, Kalaiselvi (Current Botany, 2022)
Indian ginseng, also known as Withania somnifera, is a popular medicinal plant used as a domestic treatment for a number of age-related illnesses. The field grown WS roots are referred as as a Rasayana (Rejuvenator) medication in the traditional Ayurvedic medicine of India. It has been utilized as the main component in many formulations to help slow down the aging process, manage stress, and be a remarkable neuroprotectant. The quantity and quality of traditionally grown plants, however, provide a considerable hurdle to their use in herbal-based products. The objective of this study was to determine the toxicity of shoots of in vitro developed W. somnifera, in Caenorhabditis elegans model and to compare the toxicological effect with that of plant shoots grown in the field. We found that biosafety is strictly concentration dependent. It was clear from the results that 250 µg/µL of W. somnifera shoot extract exhibited maximum viability for wild type animals.